A red carpet for Iron metabolism - Muckenthaler, Martina; Rivella, Stefano; Hentze, Matthias W. (Cell, 2017)
200 billion red blood cells (RBCs) are produced every day, requiring more than 2 × 1015 iron atoms every second to maintain adequate erythropoiesis. These numbers translate into 20 mL of blood being produced each day, containing 6 g of hemoglobin and 20 mg of iron. These impressive numbers illustrate why the making and breaking of RBCs is at the heart of iron physiology, providing an ideal context to discuss recent progress in understanding the systemic and cellular mechanisms that underlie the regulation of iron homeostasis and its disorders.